Ambivalent Stances of Translanguaging Pedagogy in Indonesia: A Nexus Case Study - Yohanes Kurniawan Winardi; Eka Fadilah; Yulius Kurniawan (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2025)
The primary objective of this research article is twofold: First, it examines the perspectives of Indonesian higher school students regarding the use of translanguaging both within and outside the classroom. Second, it analyzes the potential implications of translanguaging practices on their future careers. Adapting a nexus case-study framework, the study purposively selected five participants among 38 students who were pursuing a degree in economics at a private institution in Surabaya, Indonesia. The data were collected through classroom observations, participant reflections, and focus group discussions, then analyzed thematically to trace connections among historical bodies, interactional orders, and discourses in place. The findings reveal that the participants hold loose and gain viewpoints toward translanguaging. While the participants recognize the learning value of small group debates, they prefer to use only English during classroom lectures, reflected by the interplay between their linguistic histories, real-time classroom interactions, and broader societal ideologies monolingual space emerges when individuals conform to the ideals espoused by their social groupings. The participants’ alignment with monolingual norms is shaped by institutional expectations and imagined futures where English accuracy and fluency signals professionalism. Although translanguaging supports learning, they fear its overuse may constrain career advancement. The consequences of these findings are further discussed in the closing portion of this work.